Comparison of Anterior Decompression and Fusion With Posterior Laminoplasty for Multilevel Cervical Compressive Myelopathy. Issue 8 (October 2015) - Jiang, Lianghai; Tan, Mingsheng; Dong, Liang; Yang, Feng; Yi, Ping; Tang, Xiangsheng; Hao, Qingying
<x xml:space="preserve">Abstract</x> Study Design: Systematic review and meta-analysis. Objective: To evaluate anterior decompression and fusion compared with posterior laminoplasty when treating multilevel cervical compressive myelopathy. Summary of Background Data: Satisfactory results have been reported with both anterior decompression and fusion and posterior laminoplasty in the treatment of multilevel cervical compressive myelopathy. However, which method is safer and more effective remains controversial. Methods: MEDLINE, EMASE, and the Cochrane library databases were searched for relevant controlled studies up to December 2014 that compared anterior decompression and fusion with posterior laminoplasty for the treatment of multilevel cervical compressive myelopathy. The following outcome measures were extracted for analysis: preoperative and postoperative Japanese Orthopedic Association scores, neurological recovery rate, preoperative and postoperative overall Cobb angle, blood loss, operative time, surgical complications, and reoperation rate. Results: A total of 19 studies representing 1279 patients were included in this analysis. The results indicated that anterior decompression and fusion was associated with better postoperative neurological function (P=0.001), a higher recovery rate (P<0.01), and better cervical alignment (P<0.01) than posterior laminoplasty in the treatment of multilevel cervical compressive myelopathy. However, anterior decompression and fusion was also associated with higher postoperative complication (P<0.01) and reoperation (P<0.01) rates. Intraoperative blood loss (P<0.01) was higher and operative times (P<0.01) were longer in the anterior decompression and fusion group compared with the posterior laminoplasty group. Conclusion: On the basis of this meta-analysis, anterior decompression and fusion is associated with better recovery of neurological function, better postoperative cervical alignment, higher postoperative complication and reoperation rates, more blood loss, and longer operative times compared with posterior laminoplasty.